Aortic calcification index predicts mortality and cardiovascular events in operatively treated patients with peripheral artery disease: A prospective PURE ASO cohort follow-up study - Rantasalo Ville; Laukka Dan; Nikulainen Veikko; Jalkanen Juho; Gunn Jarmo; Hakovirta Harri (United States, 2022)
Objective: The present study evaluates the association of aortic calcification with mortality and major adverse cardiovascular and leg events (MACEs and MALEs) in patients with peripheral artery disease (PAD). The risk for mortality and MACEs and MALEs is considered in clinical decision-making.
Methods: This cohort found in 2012-2013 consists of 226 patients with symptomatic PAD referred to Turku University Hospital for invasive treatment. Follow-up data about mortality and survival without MACEs and MALEs were collected up to 5 years from the inclusion date, and aortic calcification index (ACI) was measured from patients with available imaging studies (164 of 226). ACIs' association with events and mortality was evaluated in Cox regression, Kaplan-Meier, and classification and regression tree analysis.
Results: All-cause mortality at 1, 3, and 5 years was 13.7% (31), 26.1% (59), and 46.9% (106), respectively. In multivariable Cox regression analysis, ACI and ACI > 43 were independent risk factors for all-cause mortality (hazard ratio [HR]: 1.13 per 10 units, 95% confidence interval [CI]: 1.00-1.22 and HR: 1.83, 95% CI: 1.01-3.32, respectively) and for MACEs (HR: 1.10 per 10 units, 95% CI: 1.00-1.22 and HR: 3.14, 95% CI: 1.67-5.91, respectively), but not for MALEs. Classification and regression tree analysis showed that ACI = 43 best divides cohort in relation to mortality. Kaplan-Meier analyses showed that ACI > 43 is associated with greater mortality and occurrence of MACEs compared with those who have ACI ≤ 43 (log-rank P value .005 and .0012, respectively).
Conclusions: Risk for mortality and MACEs is associated with high ACI. ACI can expose the risk in patients with PAD for further cardiovascular events and mortality.